PENGEMBANGAN E-BAHAN AJAR MENGGUNAKAN BOOK CREATOR BERBASIS RADEC BERBANTUAN MIND MAP PADA MATERI PERTUMBUHAN MANUSIA PADA KELAS V SEKOLAH DASAR - Mesy Kurnia; Risda Amini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study was motivated by the limited use of digital teaching materials in elementary schools, particularly in science education in fifth grade. Teachers still predominantly use printed teaching materials, such as textbooks and workbooks, as well as lecture methods, which cause students to be less motivated, tend to be passive, and the learning process becomes less optimal in increasing students' interest and understanding. This study aims to develop e-learning materials using Book Creator based on RADEC with the assistance of Mind Map on the subject of Human Growth that are valid and practical. The type of research is Research and Development (R&D) using the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. Based on the validity test results by subject matter experts, language, and media experts, the developed e-learning materials were categorized as highly valid, with an average score of 91.7%. The pilot testing was conducted at SD Negeri 32 Bungo Pasang and SD Negeri 29 Dadok Tunggul Hitam, while the implementation was carried out at SD Negeri 08 Pangkalan. Practicality tests involving teachers and students at the pilot schools and research sites showed that the e-learning materials are highly practical for use in teaching. When averaged across all schools, the practicality percentage of the e-learning materials reached 92.38% from teachers and 88.97% from students. Therefore, it can be concluded that the e-learning materials using Book Creator based on RADEC assisted by mind maps on human growth material in fifth grade elementary school are proven to be highly valid and practical for use in learning. Keywords: E-learning materials, Book Creator, RADEC assisted by Mind Map, ADDIE